2021
DOI: 10.21203/rs.3.rs-549763/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triglyceride/High-Density Lipoprotein Cholesterol Ratio is associated with the mortality of COVID-19: An Observational Study

Abstract: (1) Background: Triglyceride to high density lipoprotein cholesterol (TG/HDL-c) ratio is crucial when researching metabolic and vascular diseases, and its involvement in COVID-19 was sparsely elaborated on. The purpose of the study was to explore if there were any associations between the TG/HDL-c ratio and COVID-19 prognosis; (2) Methods: A total of 262 COVID-19 patients were retrospectively investigated. The clinical features and baseline hematological parameters were recorded and analyzed; (3) Results: Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…These results aligned with a prior study that found higher levels of IL-6, IL-1β, and MCP-1 in IPAH patients with elevated TG/HDL17. Furthermore, Peng et al discovered that a higher TG/HDL ratio was associated with an increased risk of COVID-19 death in instances of COVID-19 pneumonia 30 .…”
Section: Discussionmentioning
confidence: 99%
“…These results aligned with a prior study that found higher levels of IL-6, IL-1β, and MCP-1 in IPAH patients with elevated TG/HDL17. Furthermore, Peng et al discovered that a higher TG/HDL ratio was associated with an increased risk of COVID-19 death in instances of COVID-19 pneumonia 30 .…”
Section: Discussionmentioning
confidence: 99%